Skeletal muscle carnitine metabolism during intense exercise in human volunteers - Shannon, C.E. (2016)
Increasing skeletal muscle carnitine content enhances PDC flux during 30 minutes of continuous exercise at 80% Wmax, reducing reliance on non-mitochondrial ATP production and improving work output. These studies in healthy volunteers evaluated a carnitine feeding strategy that did not rely on the high carbohydrate load previously used, then investigated whether manipulating muscle carnitine could alter the adaptations to a period of submaximal high-intensity intermittent training (HIT). The rate of orally ingested 2H3-carnitine uptake into skeletal muscle was directly quantified for the first time in vivo and increased 5-fold following ingestion of an 80g carbohydrate formulation. This positive forearm carnitine balance was entirely blunted when the carbohydrate load was supplemented with 40g of whey protein, suggesting a novel antagonisation of insulin-stimulated muscle carnitine transport by amino acids. Skeletal muscle biopsy sampling demonstrated minimal acetylcarnitine accumulation and non-mitochondrial ATP production during single-leg knee extension at 85% Wmax, suggesting that PDC flux does not limit oxidative ATP production under these conditions. Conversely, PDC flux declined over repeated bouts of cycling at 100% Wmax, as evidenced by greater non-mitochondrial ATP production in the face of similar acetylcarnitine accumulation. This suggested that muscle carnitine availability could influence oxidative ATP delivery during submaximal HIT. Manipulation of muscle carnitine content by daily carnitine/carbohydrate feeding elevated free carnitine availability and maintained PDC flux during repeated bouts of intense exercise. However, profound improvements in oxidative ATP delivery in response to HIT eclipsed any effect of this carnitine-mediated increase in PDC flux on non-mitochondrial ATP production and indeed, carnitine supplementation did not potentiate any increases in exercise capacity above submaximal HIT alone. These novel data advance our understanding of muscle carnitine transport and the interplay between carnitine metabolism, PDC flux and non-mitochondrial ATP production during intense exercise, having important implications for the development of nutritional and exercise prescription strategies to enhance human performance and health.